Lithographically engineered shallow nitrogen-vacancy centers in diamond for external nuclear spin sensing. (22nd August 2018) - Fukuda, Ryosuke; Balasubramanian, Priyadharshini; Higashimata, Itaru; Koike, Godai; Okada, Takuma; Kagami, Risa; Teraji, Tokuyuki; Onoda, Shinobu; Haruyama, Moriyoshi; Yamada, Keisuke; Inaba, Masafumi; Yamano, Hayate; et al.
Abstract: The simultaneous control of the number and position of negatively charged nitrogen-vacancy (NV) centers in diamond was achieved. While single near-surface NV centers are known to exhibit outstanding capabilities in external spin sensing, trade-off relationships among the accuracy of the number and position, and the coherence of NV centers have made the use of such engineered NV centers difficult. Namely, low-energy nitrogen implantation with lithographic techniques enables the nanoscale position control but results in degradation of the creation yield and the coherence property. In this paper, we show that low-energy nitrogen ion implantation to a 12 C (99.95%)-enriched homoepitaxial diamond layer using nanomask is applicable to create shallow NV centers with a sufficiently long coherence time for external spin sensing, at a high creation yield. Furthermore, the NV centers were arranged in a regular array so that 40% lattice sites contain single NV centers. The XY8- k measurements using the individual NV centers reveal that the created NV centers have depths from 2 to 12 nm, which is comparable to the stopping range of nitrogen ions implanted at 2.5 keV. We show that the position-controlled NV centers are capable of external spin sensing with a ultra-high spatial resolution.